STUDI POPULASI Apis cerana (Hymenoptera:Apidae) PADA KEBUN CAMPUR DI DESA PAGAR PUDING KECAMATAN TEBO ULU KABUPATEN TEBO JAMBI - Darmawan, Adi - (Pendidikan Biologi, 2014)
Apis cerana is an insect that is often found nesting in tree cavities . In connection with it has conducted research on population studies of Apis cerana ( Hymenoptera : Apidae ) in the mixed garden fence in the village of Pagar Puding Tebo Tebo Ulu Jambi in January to February 2014, with the aim to determine the population of Apis cerana nest height which includes the study of surface soil , stem diameter , width and length of the nest.This study used a descriptive survey method by observing directly Apis cerana colonies were found in the village of Pagar Puding District of Jambi Tebo Tebo Ulu which measure the height of the nest from the ground surface, stem diameter, width and length of nests and nesting species. From the research conducted found a nest of Apis cerana populations are found as many as four nests per hectare, stem diameter ranged from 43.94 to 79.28 cm , height from ground nests ranged from 1.14 to 2.34 m, the length of nests ranged from 6-30 cm long, 3-9 cm wide nest. Plant for put is nest are Lansium domesticium and Havea brasiliensies.